Model Pengembangan Sumber Daya Manusia Kementerian Pertahanan Era Society 5.0 Guna Meningkatkan Pertahanan Negara - Faonaso Harefa; Tati Herlia; Mohadib (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2026)
The study aims to formulate a model of human resource development (HR) within the Ministry of Defense in facing the challenges of the Society 5.0 era to improve its function and strategic role in national defense. The approach used is qualitative with triangulation design, while data analysis is carried out using NVivo 12 software to explore information in depth and systematically. The results showed that human resource competencies in the Ministry of Defense had shown an increase from year to year. However, the dynamics of the rapid development of science and technology as well as the changing global geopolitical situation provide a significant challenge in the process of developing the HR. Therefore, an HR development model is needed that is not only adaptive to changes in the strategic environment but also based on national values. The development of human resources in the Ministry of Defense must integrate the values ​​of Pancasila as the foundation of idiil, the 1945 Constitution of the Republic of Indonesia as a constitutional foundation, as well as upholding the ethics and integrity of the profession through the practice of Sapta Marga, the Oath of Soldiers, Eight Mandatory TNI, and Panca Prasetya Korpri. Thus, it is hoped that human resources will be formed that are not only professional and knowledgeable but also have a strong national character and are able to answer the demands of the times productively and innovatively and have a noble character. This study made an important contribution to the formulation of strategic policies for developing defense human resources relevant to national needs in the digital era and globalization.